PENGELOLAAN PESERTA DIDIK BARU DALAM MEWUJUDKAN SISWA BERPRESTADI DI MI DARUL ULUM SARIROGO - M. Athoiful Fanan; Nur Chofifah; Maria Ulfa (ICO EDUSHA, 2022)
This research concerns student management in realizing outstanding students at MI Darul Ulum as a case study material. Student management is the management of students in schools or madrasas starting from the analysis of student needs, placement through graduation to becoming alumni students. This study aims to identify student management in realizing outstanding students at MI Darul Ulum so that student management can be understood by researchers. Starting from identifying the management of student management at MI Darul Ulum to being able to realize outstanding students at the school. This research is a form of qualitative approach that produces qualitative descriptive data where data collection is carried out by means of observation and interviews so as to be able to dig deeper into the management of student management so as to be able to realize outstanding students at MI Darul Ulum, this approach is an approach that presents actual facts what's in the field. The results of this study are 1). Student management in realizing student achievement at MI DARUL ULUM. 2). The development of student achievement is developed through intelligence and hobbies possessed by students both in terms of subjects or academic and non-academic. The benefit of this research is to find out how to manage student management which is able to realize students who excel in school. Keywords: Management, Students, Achievement References Jahari, Jaja, Heri Khoiruddin, and Hany Nurjanah, ‘P-ISSN: 2541-383X e-ISSN: 2541- 7088 Manajemen Peserta Didik’, Isema, 3.2 (2018), 170–80 Hasil observasi dengan WAKA kesiswaan di Sarirogo yang juga bekerja sebagai pengajar di MI Darul Ulum Sarirogo pada Hari Senin jam 08.23 tanggal 31 Oktober 2022 Fathinahaya Nailatsani and others, ‘Pengaruh Manajemen Peserta Didik Sekolah Menengah Pertama Terhadap Prestasi Belajar’, PANDAWA : Jurnal Pendidikan Dan Dakwah, 4.1 (2022), 200–213ejournal.stitpn.ac.id. Suminar, Wahyu, ‘UNTUK MENINGKATKAN PRESTASI SISWA PADAPendahuluan Pendidikan Harus Mencetak Produk Lulusan Yang Unggul Tidak Hanya Dari Segi Intelektual Melainkan Juga Spiritual Dan Sosialnya . Pendidikan Merupakan Usaha Manusia Untuk Menumbuhkan Dan Mengembangkan P’, Muslim Heritage, 1.2 (2017), 389–406 Jahari, Khoiruddin, and Nurjanah. Lukman Nul Hakim, ‘Ulasan Metodologi Kualitatif: Wawancara Terhadap Elit’, Aspirasi,4.2 (2013), 165–72. Nailatsani, Fathinahaya, Farid Setiawan, Diah Anita Aryulina, Aldi Al Husaini, Ghaida Yasmin, Nur Harjanti, and others, ‘Pengaruh Manajemen Peserta Didik Sekolah Menengah Pertama Terhadap Prestasi Belajar’, PANDAWA : Jurnal Pendidikan Dan Dakwah, 4.1 (2022), 200–213 Nilamsari, Natalina, ‘Memahami Studi Dokumen Dalam Penelitian Kualitatif’, Wacana, 13.2 (2014), 177–81 Hasil Wawancara dengan WAKA kesiswaan di Sarirogo yang juga bekerja sebagaipengajar di MI Darul Ulum pada Hari Senin jam 10.30 tanggal 31 Oktober 2022 Hasil dokumentasi dari observasi dengan staff tata usaha di Sarirogo yang juga bekerja sebagai pengajar di MI Darul Ulum pada Hari Senin jam 09.20 tanggal 21 November 2022